A User Study Comparing Two Low-Cost Chair Interfaces for Embodied Virtual Locomotion - Kitson, Alexandra; Nguyen-Vo, Thinh; Hashemian, Abraham M.; Stepanova, Ekaterina R.; Riecke, Bernhard E. (Psychonomic Society 58th Annual Meeting, 2017)
Currently, there is a rise in popularity of immersive virtual reality (VR), yet movement in VR remains a large challenge. Traditional interfaces, e.g., joysticks, often leave the user feeling disoriented or motion sick because of a sensory mismatch between visual and vestibular cues; room-scale VR has space constraints that do not allow users to virtually travel long distances. One solution is to use subtle, real-world physical motions to provide vestibular cues and match the user’s visual experience. We designed two interfaces with the HTC Vive: 1) An office chair that tracks the backrest and head mounted display (HMD) to provide forward, backward, left, and right movement as well as rotations corresponding to user's movements; 2) NaviChair: an ergonomic stool that sits atop a Wii Balance Board and senses user’s center of mass shifts to move. Users were tasked to find 8 objects randomly hidden in 16 boxes. After, we interviewed them about their experience. Users found the embodied chair interfaces were easy to learn, natural and comfortable to use, and precise to locomote without significant motion sickness. These results suggest embodied chair interfaces are promising for movement in VR.
Keywords: Riecke; Riecke_2017; abraham-hashemian; alex-kitson; bernhard-riecke; katerina-stepanova; leaning-based interfaces; motion cueing; motion-cueing; proj--motionCueingInterfaces; spatial updating; talkWithoutPaper; thinh-nguyen-vo